Indium distribution and correlations in polymetallic veins from Pingüino deposit, Deseado Massif, Patagonia, Argentina - Jovic, Sebastian Miguel (2011)
The Pingüino deposit is characterized by the presence of indium-rich polymetallic vein mineralization representing an atypical epithermal occurrence for the low sulphidation epithermal mineralization from the Deseado Massif, Patagonia, Argentina. Polymetallic veins display high In, Zn, Pb, Ag, Cd, Au, As, Cu, Sn, W and Bi values represented by complex sulphide mineralogy. Mineralization developed in two main stages: a Cu-Au-In-As-Sn-W-Bi stage, and a Zn-Pb-Ag-In-Cd-Sb stage. Correlation coefficients are used to estimate the degree of inter-relation between metals concentrations in each stage and specifically to determinate the behaviour of indium. Indium concentrations show a wide range (3.4–1184 ppm In) and, based on the correlation coefficients of ore geochemistry, in the first stage indium is associated mainly with Sn, present in ferrokesterite and cassiterite, while the highest indium values are related to the late mineralization stage, closely associated with Zn and Cd and present in the Fe-rich sphalerite, the most important In-bearing mineral in the deposit.